Impacts of Starch and the Interactions Between Starch and Other Macromolecules on Wheat Falling Number. Issue 3 (28th March 2019) - He, Yuezhen; Lin, Yu‐Lian; Chen, Chen; Tsai, Min‐Hui; Lin, Amy Hui‐Mei
Abstract: Wheat with a low falling number (FN) has been particularly prevalent in recent years and has resulted in a loss of more than $140 million in a single year in the wheat industry in the Pacific Northwest of the United States. FN measurement is a standard method for the evaluation of grain α‐amylase activity, and a low FN indicates a reduction in hot wholemeal paste viscosity due to sprouting damage. Recent studies show that a low FN may result from a developmental change of starch and adverse effects of non‐α‐amylase macromolecules on wheat. In this review, we describe the principles of FN measurement and the relationship between FN and α‐amylase. We also discuss the isozymes, locations, and inhibitors of wheat α‐amylase. The effects of various aspects of starch, which is the substrate of α‐amylase, on wheat FN are also discussed, including starch structural characteristics (for example, starch granule architecture), starch susceptibility to α‐amylase, and the interaction between starch and nonstarch macromolecules (for example, lipids). Studies on the effects of planting environments (for example, temperature) and agronomic practices (for example, irrigation and fertilization) on both starch paste viscosity and FN are also reviewed. This paper highlights the importance of considering the impacts of starch and the interactions of starch and other macromolecules, including wheat α‐amylase, on wheat FN, which is important for developing strategies to solve the low FN problem.